The genotoxic and cytotoxic effects of nimesulide in the mouse bone marrow. (July 2014) - Tripathi, Rina; Tripathi, Pankaj; Pancholi, Shyam S.; Patel, Chhagan N.
Abstract Genotoxicity of nimesulide (NM) was evaluated by employing bone marrow (BM) chromosomal aberration (CA) and micronucleus assays in Swiss albino mice. For BM CA assay, mice of either sex were treated orally with 1.5, 2.5 and 5 mg body weight solution of NM in 0.2 mL of 0.05% CMC (carboxy methyl cellulose) daily for 4, 13, 28 and 40 weeks. Treatment induced dose-dependent and significantly depressed mitotic activity and increase in CAs per cell in the BM cells after 13 weeks of treatment at all dose levels. In micronucleus assay, male mice were treated orally with the same dose levels and sampling durations as for CA assay. Treatment increased the percentage of micronucleated polychromatic erythrocytes frequency and showed a statistically significant reduction in polychromatic erythrocyte/normochromatic erythrocyte ratio, as compared to control groups. Cyclophosphamide (40 mg/kg) was used as clastogen (positive control) and yielded the expected positive results. Cytotoxicity was observed in the 8-week recovery period after 40 weeks of dosing, but it was not significant. On the basis of these findings, it may be concluded that in the long term, NM, or its biotransformed product, is genotoxic and cytotoxic for BM cells of mice in vivo.